E-Learning and Augmented Reality (AR) for chronic wound assessment: promoting learning and quality of care - Jorge, Nelson (2019)
This investigation aimed to verify if augmented reality (AR) increases students' motivation and enhances the development of clinical decision-making skills in wound diagnosis and treatment. A quasi-experimental study was carried out with a sample of 54 nursing students. A comparative analysis of the progress of the control and experimental group was made using the data extracted from the simulator and a questionnaire. First, both groups used e-FER, a virtual simulator that simulates the diagnosis and treatment of virtual clinical cases. In the second moment, the control group continued using only e-FER, while the experimental group used e-FER combined with an AR application to observe the chronic wounds. The results showed that AR enhanced student performance, particularly in wound diagnostic parameters, with highly statistically significant differences (p<0,001), and registering high levels of motivation and simulator usability, even with the introduction of an additional device in the activity.